Forefathers Part III as a Masterpiece - Emrah GAZNEVİ (Ankara Üniversitesi Dil ve Tarih-Coğrafya Fakültesi Dergisi, 2016)
19 century witnessed signicant changes in the eld of literature and art in addition to certain turning points for many European countries. These changes were so inuential that they paved the way for a new movement. This new movement was romanticism which was a reaction to classicism opposing all its aesthetics and principles. One of the most important poets of this movement as well as Polish literature, is Adam Mickiewicz. Especially his work Dziady (Forefathers) is important in that it was meant to give hope to his nation under captivity, then. This study aims to examine how Mickiewicz addresses to the feelings of his people, concepts that he introduces to poetry, his religious approach and how he conveys, in his poems, what needs to be done in the struggle of independence for his nation.